2003
DOI: 10.1017/s0022112002003348
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional acoustic-roughness receptivity of a boundary layer on an airfoil: experiment and direct numerical simulations

Abstract: The paper is devoted to an experimental and numerical investigation of the problem of excitation of three-dimensional Tollmien–Schlichting (TS) waves in a boundary layer on an airfoil owing to scattering of an acoustic wave on localized microscopic surface non-uniformities. The experiments were performed at controlled disturbance conditions on a symmetric airfoil section at zero angle of attack. In each set of measurements, the acoustic wave had a fixed frequency fac, in the range of unstable TS-waves. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 50 publications
(64 reference statements)
0
8
0
2
Order By: Relevance
“…After this recalculation, the initial phase of the vibrations becomes equal to zero. As was indicated by Würz et al (2003), phases of this kind are convenient for extrapolation of the receptivity characteristics to the zero frequency of vibrations and for comparison of these characteristics with those obtained at scattering of the free-stream disturbances on steady surface non-uniformities. In the present case, this point is important for comparison of the obtained receptivity phases with those obtained in experiments by Borodulin et al (2008bBorodulin et al ( , 2013.…”
Section: Resonant Spectra Of Surface Vibrationsmentioning
confidence: 99%
“…After this recalculation, the initial phase of the vibrations becomes equal to zero. As was indicated by Würz et al (2003), phases of this kind are convenient for extrapolation of the receptivity characteristics to the zero frequency of vibrations and for comparison of these characteristics with those obtained at scattering of the free-stream disturbances on steady surface non-uniformities. In the present case, this point is important for comparison of the obtained receptivity phases with those obtained in experiments by Borodulin et al (2008bBorodulin et al ( , 2013.…”
Section: Resonant Spectra Of Surface Vibrationsmentioning
confidence: 99%
“…In the following, this receptivity process was also addressed for three-dimensional roughness elements (Choudhari & Kerschen 1990;Tadjfar & Bodonyi 1992) interacting with different types of free-stream disturbances. Würz et al (2003) found an increased receptivity towards external, in that case acoustical, disturbances for non-zero spanwise wavenumbers of the roughness element in their experimental and numerical investigations. Further details on the receptivity process are reviewed by Kachanov (2000) and Saric, Reed & Kerschen (2002).…”
mentioning
confidence: 94%
“…A linear relationship inbetween roughness height and generated TS-wave amplitude is only present below a certain threshold value for the roughness height. Furthermore, experimental and numerical results by Wuerz et al 7 show an increased receptivity for non-zero spanwise wave numbers of the roughness element towards external, in that case acoustical, disturbances.…”
Section: Introductionmentioning
confidence: 94%